Quando o novo evidencia o ultrapassado: contratos internacionais eletrônicos, diálogo de fontes e afirmação da autonomia da vontade - Lucas Sávio Oliveira da Silva (2016)
Amongst the main sectors of Private International Law is the definition of the law applicable to international cases. In Brazil, the objective connecting rule for international contracts is to apply the law of their constitutions location. This fact runs counter to what is observed in most States, whose legal systems guarantee parties prerogative of defining themselves which legal system or rules of law will govern their covenants, especially if they are professionals signing business contracts. The Brazilian general rule is proved even more inadequate when analyzed in a context of electronic commerce, in which the characteristics of the Internet, used as a means for the parties to contract, make locator methods ineffective. However, an analysis of the Brazilian legal system, based on the theory of dialogue of sources, shows that, in fact, what is missing is coherence to the system, since in certain contexts freedom of choice is already a reality in Brazil. It is argued, based on comparative analysis of norms and the mentioned dialogue of sources theory, that its ratification will bring legal certainty to electronic international contracting.